PENGARUH KUALITAS PRODUK DAN PELAYANAN TERHADAP KEPUASAN KONSUMEN (STUDI PADA CARREFOUR LEBAK BULUS - JAKARTA) - Achmad Tarmizi (Jurnal Ilmiah Multidisiplin, 2022)
Costumer satisfaction is the main for hypermarket employees to give the best quality of service. Then every costumer wants to expense more for service quality which can make happy the customer to be served as at their home. Customer service could be seen after the customers use the product of service. With other word, customer satisfaction is after service evaluation or evaluation after comparing what they feel with their hope. The research aim is to know “product quality affect and service quality to customer satisfaction (Study on Carrefour of Lebak Bulus, Jakarta. The research result show that affect variable of product quality and service quality affect significantly to customer satisfaction of Carrefour of Lebak Bulus. T test result take thitung value accepted at 5% significant, quality service variable affects dominantly to customer service comparing with product quality variable. T test result take thitung value for quality service variable (7.444) more than thitung value product quality variable (3.308) at significant of 5%.